Time to sweat the assets? The analysis of two airport cases of restricted capacity in different continents - Miguel Mujica Mota; Mota Geert Boosten; Catya Zuniga (Organisation for Economic Co-operation and Development (OECD), International Transport Forum, 2017)
Air traffic numbers have been steadily increasing and are projected to so in the future. Most traffic growth pertains to a small fraction of the total available airport capacity worldwide; particularly the main airport hubs present these trends. As a consequence, they are becoming increasingly congested, which results in the increase of delays and reduction of reliability. For these reasons it is important to look for ways in which the existing assets can take up more traffic. These solutions should go beyond long-term considerations to build more infrastructures. In the current paper we discuss of different ways of increasing capacity. First we define capacity and then we discuss techniques for identifying bottlenecks and room for improvement. We exemplify them by providing two examples of airports in different continents, Schiphol Airport and Mexico City Airport.
Keywords: 330; Flughafenmanagement; Flughafeninfrastruktur; Kapazitätsplanung; Mexiko; Niederlande